Pengaruh Harga dan Rating Produk terhadap Keputusan Pembelian Produk Skincare Skintific di E-Commerce Berdasarkan Data Sekunder dari Shopee & Tokopedia - Zulaika, Siva (Keizai, 2024)
This research was conducted with the aim of finding out the influence of price and product rating on purchasing decisions for skincare products on e-commerce Shopee and Tokopedia. This research uses quantitative methods with causal associative research characteristics, using secondary data. The population in this study were Indonesian people who had purchased skincare skintific moisturizer products on E-commerce Shopee and Tokopedia, with a total sample of 80 shops selling skincare skintific moisturizer on E-commerce Shopee and Tokopedia which were selected using the nonprobability accidental sampling method with data in the form of a cross section. The results of the partial test (t test) of this research show that the price variable does not have a significant effect on purchasing decisions with a prob value 0.92 is greater than >0.05 then the product rating variable has a positive and significant influence with a positive coefficient value of 11.04 with a prob value 0.0001 smaller <0.05.